Conversa com Nelson Felix. - Costa, Lucas [UNESP] (Escola de Comunicações e Artes da Universidade de São Paulo, 2014)
Interview with the plastic artist Felix Nelson (Rio de Janeiro, 1954), for the master research of Lucas Costa about the unsteady processes in art. In this conversation, the artist talks about the elements that constitute a certain tension in his work and the difficulty in defining these sensations that are triggered in the creative process and intricate in a way in his work. In this context, Nelson Felix approach an artistic tradition, precisely because of the reflection on contemporary art and his own performance in the circuit.In the broadest sense, the conversation goes around the artistic activity and the power of the cultural thinking.

Entrevista realizada com o artista carioca Nelson Felix (1954), para a pesquisa de mestrado de Lucas Costa, sobre processos instáveis em arte. Nesta conversa, o artista comenta os elementos que constituem uma certa tensão em seu trabalho e da dificuldade em definir essas sensações, que são disparadas no processo criativo e inseridas no trabalho de maneira intrincada. Neste contexto, Nelson Felix se aproxima de uma tradição artística, justamente para refletir sobre a produção contemporânea e sua própria atuação no circuito.No sentido amplo, a conversa gira em torno da atividade artística, sobre a potência de um pensamento cultural.
Conversation with Nelson Felix.
Keywords: contemporary art; creative process; sculpture; Nelson Felix; arte contemporânea; processo criativo; escultura; Nelson Felix